Imaging for patient-customized simulations and systems for point-of-care ultrasound : International Workshops, BIVPCS 2017 and POCUS 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 14, 2017, Proceedings /: International Workshops, BIVPCS 2017 and POCUS 2017, held in conjunction with MICCAI 2017, Québec City, QC, Canada, September 14, 2017, Proceedings. (2017) - Unknown
No abstract available